Hubungan Hafalan Al-Qur’an Dengan Hasil Belajar Peserta Didik Pada Mata Pelajaran Matematika DI SDTQ-T An Najah Cindai Alus Martapura - Muhammad Iqbal Ansari; Afrina Nafliani; Barsihanor; Sari Kumala (JIEES : Journal of Islamic Education at Elementary School, 2021)
Memorizing theAl- Qur’an is a process carried aut by memorizing the Al-Qur’an, of caurse after the process of reading the Al-Qur’an properly and correctly, but there is also a process of memorizing by learning the contents of the verses of the Al-Qur’an first then memorize it. In the learning outcomes obtained by the development of the mindset of the cognitive, affective and psychomotor domain. Therefore, the more reading, understanding, remembering and memorizing then Al-Qur’an it can affect the result of mathematics lessons or other lessons. The motivation behind this review is to decide the impact of capacity to remember Al-Qur'an, understudies' disposition, and connections the two of them towards understudies' learning results in science. The exploration strategy utilized is the correlational review technique, the quantity of test are 60 understudies from two classes who lead retention of Al-Qur'an. Information assortment was finished by utilizing poll appropriation and test strategy. Information investigation utilizing relationship examination and numerous relapse techniques. The factual test utilized was t test and F test. Information investigation utilized relationship and relapse strategies (basic and plural). From the examination results tracked down that: (1) there is a huge impact between the capacity to peruse Al-Qur'an towards arithmetic learning results (r = 0.883 and Ŷ = 1,276 + 1,182X1). (2) there is critical impact between understudies' mentality towards arithmetic learning results (r = 0.876 and Ŷ = 0.509 + 0.138X2). (3) there is critical impact between the capacity to remember Al-Qur'an and understudies' demeanor towards mathematicsmlearning results (r = 0.893 and Ŷ = 0.183 + 0.062X1 + 0.689X2)